Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1592/phco.21.1.1.34444
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency and Cost of Patient‐Initiated Device Removal in the ICU

Abstract: Patients commonly remove medical devices on their own, and this represents significant consumption of health care resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 19 publications
1
29
0
3
Order By: Relevance
“…Patients who remove these devices stay longer in intensive care, present persistent agitation and greater daily needs for boluses of sedation and analgesic than those who do not face this incident, (5) besides the family dissatisfaction and damages resulting from these situations. (6) Allied to these facts, the total cost estimated for removed devices (tubes, drains and catheters) is approximately U$7.606 and the cost/event is U$181.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who remove these devices stay longer in intensive care, present persistent agitation and greater daily needs for boluses of sedation and analgesic than those who do not face this incident, (5) besides the family dissatisfaction and damages resulting from these situations. (6) Allied to these facts, the total cost estimated for removed devices (tubes, drains and catheters) is approximately U$7.606 and the cost/event is U$181.…”
Section: Introductionmentioning
confidence: 99%
“…(6) Allied to these facts, the total cost estimated for removed devices (tubes, drains and catheters) is approximately U$7.606 and the cost/event is U$181. (5) The authors of a study developed in the hospitalization, intensive and semi-intensive care units of a private hospital in São Paulo, in Southeast Brazil, concluded that the adverse events that occurred were related to gastrointestinal tubes, with the unscheduled removal of the tube and its obstruction being the most frequent events. (7) This fact agrees with the main incidents observed in the intensive care unit of a private hospital in the city of Rio de Janeiro, which is the setting of the present study.…”
Section: Introductionmentioning
confidence: 99%
“…In einer großen multizen trischen Beobachtungsstudie, die auf ins gesamt 49 Intensivstationen durchgeführt wurde, wurde systematisch die Häufig keit der Selbstentfernung von Kathe tern und Endotrachealtuben durch Pati enten erfasst [14]. Die Autoren fanden ei ne mittlere Prävalenz von 22,1/1000 Pa tiententagen, aber in einer anderen Stu die [5] wurde auch von einer Prävalenz von 125,6/1000 Patiententage berichtet. Vermeidungsstrategien bestehen meist in neuen/zusätzlichen physischen Fixie rungsmaßnahmen, Veränderung von Se dierungsschemata und einer verstärk ten Überwachung.…”
Section: Tab 3 Fehlermeldungen Als Hinweis Auf Ausbildungsdefizite Ounclassified
“…The cost of these patientinitiated therapeutic device removals has been estimated as high as more than $250,000 a year or $181 per event (Fraser et al, 2001). Carrion and colleagues (2000) have suggested the importance of surveillance of medical personnel and education in reducing patient-initiated accidental removal of devices.…”
Section: Costsmentioning
confidence: 99%
“…Before most of the removals (74%), significant patient agitation was documented in the chart within two hours of the accident. The annual cost associated with these removals was estimated to be more than $250,000 or $7,606 per device, or $181 per event (Fraser et al, 2001). …”
Section: Length Of Stay (Los)mentioning
confidence: 99%